Invariant points of a dynamical system of conflict in the space of piecewise-uniformly distributed measures - Koshmanenko, V. D.; Kharchenko, N. V. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We prove a theorem on the existence and structure of invariant points of a dynamical system of conflict in the space of piecewise-uniformly distributed measures.